Persepsi Kesiapan Remaja Putri dalam Menghadapi Menarche di Sekolah Dasar - Ida Baroroh; Swasti Artanti (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2022)
Menarche is the first menstruation that usually occurs in early adolescence in the middle of puberty before entering the reproductive period. Along with menstruation, there will be many accompanying events, including: hormonal reactions, biological reactions and psychological reactions, where there will be a rejection reaction in his soul to what happens to his physical condition. All of these events can be faced normally in young women, but sometimes it can also run smoothly or abnormally. The purpose of this study is to determine the description of the readiness of young women in facing menarche at the Kuripan Lor 2 State Elementary School, Pekalongan Selatan District, Pekalongan City. This research uses descriptive exploratory method, with a cross sectional design. The sampling technique used total sampling with a total sample of 34 people. The results of the Perception of Young Women's Readiness in Facing Menarche showed that more than half of the respondents were not ready to face menarche. The perception of young women's readiness to face menarche depends on the readiness of young women physically and psychologically in facing menarche.